Digital Marketing Strategies and Consumer Purchase Decisions: Empirical Evidence from Zomato - Hussain, James; Hussain, Faiyaz (Journal of Economics and Management, 2025)
In the evolving digital economy, companies increasingly leverage online marketing tools to influence consumer purchase decisions. This study investigates the impact of four key digital marketing strategies—Search Engine Optimization (SEO), personalized marketing, push notifications, and social media engagement—on consumer buying behavior, with Zomato as a case study. A quantitative approach was adopted, involving 300 active Zomato users, and data were analyzed using multiple regression analysis. Results reveal that all four strategies significantly affect purchase decisions, with push notifications and personalized marketing exerting the strongest influence. However, multicollinearity among predictors suggests overlapping effects that require advanced analytical techniques for more accurate modeling. This research contributes to both academic and industry discourse by offering actionable insights for enhancing digital engagement in app-based services.